Coarse-Grained Molecular Dynamics Simulation of DPPC Lipid Bilayers: Size Effect on Structural and Dynamic Properties (Communications in Computational Physics, 2018)
Coarse-grained molecular dynamics simulations of DPPC lipid bilayers wereperformed with different system sizes at T = 323 K for a period of 1 µs. The structuralproperties of the systems were demonstrated by examining the area and volume perlipid, electron density profile, order parameter, and the lipid bilayer thickness. It wasshown that the finite system size has a negligible effect on the ensemble averages of thearea and volume per lipid, the order parameter, and the bilayer thickness. However,the electron density profiles become smoother and wider at a larger system size due tothe increasing surface/interface fluctuation from undulations. On the other hand, thelipid dynamics was quantified by computing the lateral diffusion coefficients of DPPCmolecules. It was revealed that, the effective lateral diffusion coefficient of DPPC increasesinitially by 19% as the bilayer increases from 64 to 256 lipids per leaflet, andthen it changes slightly and fluctuates around a steady value as the system furtherexpands.
Keywords: Molecular dynamics; coarse-grained model; DPPC lipid bilayer; system size effect.